Pengaruh Pemberian Berbagai Konsentrasi Garam dan Frekuensi Penyiraman terhadap Pertumbuhan, Hasil, dan Kadar Flavonoid pada Tanaman Sweet Basil (Ocimum basilicum) - Saputro, Agusti Ardiansyah; Armita, Deffi; Nihayati, Ellis (Agrotechnology Research Journal, 2022)
Salt stress and infrequent watering application obstruct sweet basil growth and yield. But both condition can increase flavonoid production. The aim of this research is to get tolerant level of sweet basil plant on various salt concentration and watering frequency with several parameters consists of growth, yields, and flavonoid contents. The research was conducted from October 2021-January 2022 at the greenhouse of Petahunan Village, Pasuruan City. The method used was a factorial of randomized block design with various watering frequency consisist of once a day (W0), once on two days (W1), and once on three days (W2). Various salt concentration consists of 0 ppm (N0), 1000 ppm (N1), 2000 ppm (N2), 3000 ppm (N3), and 4000 ppm (N4). There is an interaction between saline medium and infrequence watering, whenever with more watering can decrease saline effect on plant primary metabolism. Interaction betweet saline medium and infrequence watering inhibit plant vegetative growth. But saline that interaction can improve sweet basil yields such us flowers, seeds, and also flavonoid contents on leaves. The research conclusion is that interaction between saline medium and infrequence watering obstructed vegetative growth, but increase  yields and flavonoid contents.